Melatonin as an immunomodulator in combined therapy of herpesvirus skin diseases associated with HIV - Dorosh, Diana; Liadova, Tetiana; Mykola, Popov; Kadygrob, Iryna; Shustval , Mykola; Malantschuk, Roman (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. Highly active antiretroviral therapy is the current standard of care for patients with HIV/AIDS. Although antiretroviral therapy is etiotropic, quite effective in reducing viral load, recurrent opportunistic infections can lead to adverse effects in the management of such patients, and side effects may limit its effectiveness. Among opportunistic infections, a large group are herpesvirus infections, they are frequent manifestations of dermatological manifestations of HIV, which can sometimes lead to death. Melatonin (N-acetyl-5-methoxytryptamine) was thought to be of purely epiphyseal origin, but recent studies have shown that melatonin synthesis can occur in some other cells and organs of the human body. In addition, it was found that melatonin regulates circadian rhythms, has a number of important functions and areas of influence. Studying its structure and action, researches over the past decade have shown that melatonin enhances the immune response of T-helpers, stimulates the production of cytokines, has antioxidant properties. Due to these effects, and possibly other mechanisms yet to be determined, melatonin has been shown to reduce drug toxicity and have immunomodulatory effects. Objective: to study the effectiveness of melatonin as an immunomodulatory agent in herpesvirus skin diseases associated with HIV as part of combined therapy. Objectives of the study: to determine serum levels of CD4 + cells and to investigate changes in immunogram parameters in patients with herpesvirus infection associated with HIV before and after melatonin therapy and to compare them with the levels of the control group. Materials and methods. In the current study, HIV patients who had an acute herpesvirus infection caused by HSV-1, HSV-2, VZV, EBV, and HHV-8 were selected. Patients were divided into two groups: group I consisted of patients receiving antiretroviral therapy, valaciclovir in standard therapeutic doses and melatonin as immunomodulatory therapy, once daily, in the evening at a dose of 3 mg. Group II included patients who received antiretroviral therapy alone in combination with valaciclovir. Clinical and laboratory evaluation was performed before and after 30 days of therapeutic intervention. Patients were asked to report any complications. Results. The study involved forty HIV patients who had an exacerbation of herpesvirus infection; the levels of CD4 + cells averaged 311 ± 128. All patients received antiretroviral therapy for at least five years with a mean infection period of 10 years. The age of patients ranged from 32 to 60 years with a mean of 41.4 ± 17.2 years. After treatment, CD4 + cells were significantly higher in group I subjects receiving antiretroviral therapy in combination with valaciclovir and melatonin than in control subjects wo not receiving melatonin after one month of treatment. The level of CD4 + cells was 37 % higher in patients taking melatonin compared with the control group (p < 0.05). The current study showed that 60% of patients (12/20) had positive changes in the parameters of the immunogram (p < 0.05). Significant differences between groups, which were statistically validity in levels of CD4 + cells and immunogram parameters, indicate that melatonin had a positive effect on the state of the immune system. Conclusion. Our study has proven the beneficial effect of melatonin on the state of the immune system in patients herpesvirus skin diseases associated with HIV. Given the low toxicity of melatonin and its ability to reduce side effects and increase the effectiveness of therapeutic agents, its use may be important and significant in combination therapy in combination with highly active antiretroviral therapy.